SPATIAL DISTRIBUTION OF LEAD IN AMAONYE FOREST SOILS OF ISHIAGU COMMUNITIES IN EBONYI STATE OF NIGERIA (Nigerian Journal of Technology, 2018)
Geostatistical technique was applied to study the spatial distributions of lead (Pb) in Amaonye forest soil of Ishiagu communities in Ebonyi State, Nigeria. A total of 605 soil samples were collected at depths of 10, 20, 30, 40 and 50 cm from all grid points in an area of 1km x 1km gridded at 100 m grids and were analysed for Pb concentration. Using the ArcGIS geostatistical extension, the metal distribution was modeled and shown on concentration maps. The variogram (CO/C) ratio values obtained as 0% at 10, 20 and 30 cm, 11.1% at 40 cm and 9.9% at 50 cm indicated strong spatial dependence. The study shows that the metal has irregular spatial distribution in the studied area, with the highest accumulation around the stream channel and spread in the direction of water-flow into the forest soil as influenced by the topography of the landscape. http://dx.doi.org/10.4314/njt.v37i4.35